2017
DOI: 10.4103/2249-4863.220026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bronchial asthma and factors associated with it among higher secondary school children in Ernakulam district, Kerala, Southern India

Abstract: Context:Bronchial asthma is one of the leading causes of hospitalization and cause of frequent absenteeism among children and adolescents. Studies reporting the prevalence of bronchial asthma among adolescents from India are limited and the available studies report wide geographic variations in the prevalence of bronchial asthma.Aims:The current study was aimed to estimate the prevalence of bronchial asthma among higher secondary school children and to identify various factors associated with it in Ernakulam d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…12,13 It has been observed that school students suffer from pre-hypertension and bronchial asthma which may cause major health issues later in life. 14 There is a need to improve the physical fitness of children and adolescents. Yoga has a holistic approach which may improve physical fitness and mental status.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 It has been observed that school students suffer from pre-hypertension and bronchial asthma which may cause major health issues later in life. 14 There is a need to improve the physical fitness of children and adolescents. Yoga has a holistic approach which may improve physical fitness and mental status.…”
Section: Introductionmentioning
confidence: 99%